Kerjasama Indonesia dan Thailand dalam Menangani Kasus Illegal, Unreported, and Unregulated (IUU) Fishing di Indonesia - M. Alvin Rikzan; Hermini Susiatiningsih (Journal of International Relations Diponegoro, 2018)
Indonesia is an easy target for IUU actors (Illegal, Unreported, Unregulated) fishing due to abundant marine resources. IUU fishing is a problem that can not be underestimate because inflict many disadvantages for Indonesia. In handling IUU fishing, Indonesia requires cooperation with other countries, especially with neighbour countries to solve the problem. This research is aimed to studying the cooperation between Indonesia and Thailand in handling IUU fishing. For analyzing the cooperation, this research use liberalism theory with qualitative method, and explanatory-based research by doing some literature studies. In this research we can see that cooperation between Indonesia and Thailand produces Memorandum of Understanding (MOU) which are expected to help handling IUU fishing. With this cooperation, all the factors of IUU fishing shall be solved.